Effect of resistance training, prescribed by zone of maximum repetitions, on the muscular strength and body composition in older women - Leandro Ferreira; André Demantova Gurjão; Carla da Silva; Lilian Bucken Gobbi; Sebastião Gobbi (Universidade Federal de Santa Catarina, 2006)
The aim of this study was to verify the effect of resistance training, prescribed by zone of maximum repetitions (MR), on the body composition and muscle strength in older women. Therefore, a quasi-experimental research design was used. The sample comprised 30 older women (61.1 ± 7.3 years) without health problems that could prevent them from attending the training protocol. Maximal muscle strength was measured by means of the 1-RM test while body composition was assessed by bioelectrical impedance which followed the recommendations of a 24-hour protocol regimen prior to the assessments. The resistance training protocol comprised 3 sessions per week; 2 sets of 10-to-12 RM each session and it lasted for 12 weeks. The data were analyzed by means of descriptive statistics and Student t-test for paired samples, at p<0.05 level. No statistically signifi cant changes (p> 0.05) on body composition variables were found, except for a small decline on body mass, which, in turn, caused a small reductionon the body mass index. Increase in strength was observed (p<0.01) for both extensor and fl exor knee muscles (36.5% and 34.3%, respectively) as well as for elbows (13.7% and 16.3%, respectively). The results suggested that resistance training at maximal-repetition zone allows for muscle strength increments, however, it does not affect lean body mass or percent and absolute values of body fat in older women.p> RESUMO O objetivo deste estudo foi verifi car o efeito do treinamento com pesos, prescrito por zona de repetições máximas (RM), sobre a composição corporal e a força muscular em mulheres acima de 50 anos. Para tal,+ foi utilizada uma pesquisa do tipo quase experimental. A amostra foi composta por 30 idosas (61,1±7,3 anos), sem problemas de saúde que impedissem a prática da intervenção proposta. A força muscular máxima foi avaliada por meio do teste 1-RM e a composição corporal pela técnica de bioimpedância elétrica, com observância do protocolo de 24 horas antecedentes a cada uma das duas avaliações. O treinamento foi realizado com 3 sessões semanais, compostas de 2 séries com 10 a 12 RM para cada um dos exercícios propostos e duração total de 12 semanas. Os dados foram analisados através de estatística descritiva e do teste t de Student pareado, com nível de signifi cância de p<0,05. Não foram encontradas alterações estatisticamente signifi cativas (p> 0,05) nas variáveis de composição corporal, exceto pequena mudança na massa corporal e, por infl uência desta, no índice de massa corporal (p<0,05). A força muscular aumentou signifi cativamente (p<0,01) nos músculos extensores e fl exores dos joelhos (36,5% e 34,3%, respectivamente) e dos cotovelos (13,7% e 16,3%, respectivamente). A interpretação dos resultados sugere que a prescrição por meio de zonas de RM proporciona aumento da força muscular, contudo não altera massa corporal magra, percentual de gordura e gordura corporal absoluta, em mulheres idosas.<